2020
DOI: 10.1002/ecs2.3012
|View full text |Cite
|
Sign up to set email alerts
|

Plant invasions alter settlement patterns of breeding grassland birds

Abstract: Citation: Andersen, E. M., and R. J. Steidl. 2020. Plant invasions alter settlement patterns of breeding grassland birds.Abstract. Animals have evolved strategies to identify areas that provide the resources and environmental conditions they need to survive and reproduce. To explore how invasions by nonnative plants might disrupt this fundamental process, we evaluated settlement patterns of migratory birds that breed in grasslands being invaded by two structurally different congeneric grasses. We established 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Grassy areas with established non-native grasses are structurally different from prairies, with substantially higher grass height and cover. They have been associated with temporal and spatial shifts in breeding patterns of grassland birds (Andersen and Steidl 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Grassy areas with established non-native grasses are structurally different from prairies, with substantially higher grass height and cover. They have been associated with temporal and spatial shifts in breeding patterns of grassland birds (Andersen and Steidl 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, at a local scale, increased woody cover can cause reorganisation of mammalian herbivore communities, benefitting smaller bodied browsing herbivores over larger bodied grazers (Smit & Prins, 2015). Similarly, reorganisation of bird communities can occur with encroachment, often favouring leaf gleaning, smaller bodied invertivorous passerines over larger bodied, non‐passerine ground dwelling birds (Andersen & Steidl, 2019, 2020; Péron & Altwegg, 2015; Sirami & Monadjem, 2012). It is likely that open system specialists will be disproportionately impacted as they are area sensitive and require large open area habitats to reproduce (Andersen & Steidl, 2020; Reino et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In southeastern Arizona desert grasslands, Andersen and Steidl (2020) examined the response of Grasshopper Sparrows along a gradient of dominance ranging from 0 to 100 percent of total grass cover for two tame species of lovegrass, Lehmann lovegrass (Eragrostis lehmanniana) and weeping lovegrass (Eragrostis curvula), to examine whether structural differences between nonnative plants and the native plants that they displaced can alter the quantity of habitat available to animals, especially species with narrow habitat breadths. During the first 2 weeks of the settlement period, Grasshopper Sparrows established breeding territories on plots dominated by native grasses, which tended to be shorter and less dense but more structurally heterogeneous and floristically diverse than areas dominated by either tame species.…”
mentioning
confidence: 99%
“…As the settlement period progressed and native-dominated areas became occupied by conspecifics, Grasshopper Sparrows increasingly established territories in areas dominated by Lehmann lovegrass, which is more structurally similar to native grasses than weeping lovegrass, but did not establish territories on plots where weeping lovegrass exceeded 21 percent of grass cover. Andersen and Steidl (2020) suggested that Grasshopper Sparrows preferred areas dominated by native plants in the absence of conspecific competition, and that the species may have perceived areas dominated by Lehmann lovegrass as suitable breeding habitat and areas dominated by weeping lovegrass as unsuitable breeding habitat. In coastal sand and southern Texas plains communities, Bielfelt (2013) examined the response of Grasshopper Sparrows across a gradient of dominance of tanglehead (Heteropogon contortus), a native grass species with growth characteristics of an invasive plant that is becomingly increasingly prevalent in southern Texas, especially in areas with clay loam soils.…”
mentioning
confidence: 99%